The use of pigs vocalisation structure to assess the quality of human-pig relationship - Villain, Avelyne S; Guérin, Carole; Tallet, Céline (Peer Community Journal, 2023)

(untitled)
Studying human-animal interactions in domestic species and how they affect the establishment of a positive Human-Animal Relationship (HAR) may help us improve animal welfare and better understand the evolution of interspecific interactions associated with the domestication process. Understanding and describing the quality of an HAR requires information on several aspects of the animal biology and emotional states (social, spatial and postural behaviours, physiological and cognitive states). Growing evidence shows that acoustic features of animal vocalisations may be indicators of emotional states. Here, we tested the hypothesis that vocal structure may indicate the quality of HAR. At weaning, 30 piglets were positively handled by an experimenter who talked to and physically interacted with them three times a day, while 30 other piglets only received the contact necessary for proper husbandry. After two weeks, we recorded the behaviours and vocalisations produced in the presence of the static experimenter for 5 min. We repeated this test two weeks later, after a conditioning period during which human presence with additional positive contacts was used as a reward for all piglets. We hypothesized this conditioning period would lead to a positive human-piglet relationship for all piglets. As expected, piglets that were positively handled at weaning expressed a higher attraction toward the experimenter, and, after the conditioning, piglets that were not positively handled at weaning expressed a similar level of attraction than the positively handled ones. Piglets positively handled at weaning produced shorter grunts than the other ones, regardless of the context of recording, which may indicate a more positive affect. During reunions with the static experimenter, a more positive HAR was associated with a decrease in vocal reactivity to human proximity. However, during reunions with the experimenter providing additional positive contacts and over the conditioning, spatial proximity to the human systematically triggered shorter and higher pitched grunts, which may indicate a more positive emotional state. Results first show that changes in vocal structure are consistent with indicators of positive states in the presence of a human. Second, these changes are stronger when the human positively interact with the piglets, supposedly emphasizing a higher positive arousal state during these interactions. We show that vocalisation structure may be a promising indicator of the quality of human-pig relationship.